Spory o Kamienie na szaniec Aleksandra Kamińskiego - Karolak, Sylwia (My University, 2019)
Aleksander Kamiński’s work Kamienie na szaniec [Stones on the Barricade], first published in 1943, has precipitated several important polemics throughout recent Polish literary history. The first, had already taken place during WWII in 1943–1944. The next polemic witnessed the dawn of postwar literature in 1946–1947, while the third was played out during the so-called thaw, in 1956–1957. The last and fourth polemic taking place in 2013, is living proof as it were that Kamienie na szaniec remains a work of considerable influence, which despite the passing of the years continues to be the subject of critical analysis and discussion. Reprinted in the present volume, the most important polemics (voices concerning Kamienie na szaniec) were raised by among others, Karol Lipiński, Juliusz Garztecki, Jan Kott, Maria Straszewska, Krzysztof Teodor Toeplitz, Janusz Zabłocki, Elżbieta Janicka, Wojciech Feleszko and Przemysław Czapliński. These invaluable commentaries come to form not only an invaluable narrative on Kaminski’s book itself, but at the same time constitute a looking glass onto Poland’s recent history and its literary milieu in the respective periods of the above polemics.
The Polemic Over Aleksander Kamiński’s Kamienie na szaniec